IMPLEMENTASI PERATURAN DAERAH DKI JAKARTA NOMOR 8 TAHUN 2007 TENTANG KETERTIBAN UMUM (STUDI KASUS PENERTIBAN PKL DI MONUMEN NASIONAL) - Mega Angelia Kondorura; Ahmad Taufiq; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2016)
The research is based on the growth of street vendors in DKI Jakarta which implicatedof many problems to the environment especially The National Monument as an iconic placeof the capital city of Indonesia, DKI Jakarta. In order to tackle the problem the localgovernment of DKI Jakarta implemented district regulation of DKI Jakarta number 8 year2007 regarding public order in National Monument. The research is conducted in order to;(1) Explain implementation of district regulation of DKI Jakarta number 8 year 2007regarding public order, (2) Explain obstacles encounter the implementation of regulation.The method used in this research is a qualitative-descriptive. Using primary andsecondary data through various techniques such of interview and documentation. There are 4factors or variables as tools of analysis which importance role in public policy in order todevelop good implementation, those are: communication, sources, disposition, andbureaucracy structure.The results found that the district regulation of DKI Jakarta number 8 year 2007regarding public order that implemented in National Monument are not optimal. Theproblems are many street vendors doesn’t know about the regulation; limitless humanresources in performing policing; and the overlapping of tasks and function amongs theimplementor.Recommendation to solve the problems and the circumstances are: enhancementcoordination between implementer, engage others local government agencies or NGOs in toinvolvement on implementating the regulation, and dissemination to the public regarding theimpact caused by illegal street vendors.